Engagement Masyarakat Atas Format Akun Media Sosial Instagram BPOM di Ambon Tahun 2023 - Agusta, Mohammad Viva; Santoso, Nugroho Budi (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Public awareness regarding the importance of safe drugs and food is crucial. However, products still have the potential to be unsafe, so the community needs to be equipped with knowledge through Information, Education, and Communication (IEC). Due to advances in information technology and the increasing number of internet users, IEC can be conducted through electronic and social media to reach a wider audience. Instagram is one of the platforms used by the Indonesian Food and Drug Authority (Indonesian FDA) Regional Office in Ambon for IEC. It has the potential to serve as a medium for communicating, disseminating information, and educating the public about safe drugs and food. However, an analysis of Instagram user engagement with the content created is needed. This study aims to determine Instagram user engagement with content formats on the Indonesian FDA Regional Office in Ambon. Instagram account using quantitative research methods with a descriptive approach. The research-dependent variable is the content format (video, photo, infographic), and the independent variable is engagement (like, comment, save, share). Engagement analysis was conducted on 509 posts during 2023, consisting of 51 (10.02%) video content, 174 (34.19%) photos, and 284 (55.80%) infographics. The results of the analysis show that photo content formats have higher engagement than videos and infographics, with an average number of likes (25.03), saves (0.29), and shares (0.69). Meanwhile, video content formats have a higher average number of comments (0.14) compared to photos and infographics. This study concludes that photo and video content have higher engagement, so it can be chosen as priority content to increase follower engagement on the Indonesian FDA Regional Office in Ambon Instagram account.